Perturbation of xenobiotic metabolism in Dreissena polymorpha model exposed in situ to surface water (Lake Trasimene) purified with various disinfectants. (February 2016) - Sapone, Andrea; Canistro, Donatella; Vivarelli, Fabio; Paolini, Moreno
Abstract: Sanitation is of crucial importance for the microbiological safety of drinking water. However, chlorination of water rich in organic material produces disinfection by-products (DBPs), many of which have been reported to be mutagenic and/or carcinogenic compounds such as haloacetic acids and trihalomethanes. Epidemiological studies have suggested a link between drinking water consumption and cancer. We previously observed that Cyprinus carpio fish exposed to DBPs, may be subject to epigenetic effects such as those referable to the up-regulation of cytochrome P450 (CYP) superfamily (ex. co-mutagenesis/co-carcinogenesis and oxidative stress) that has been associated to non-genotoxic carcinogenesis. Our goal was to study the xenobiotic metabolism in mollusks exposed in situ to surface water of Lake Trasimene (Central Italy) treated with several disinfectants such as the traditional chlorine dioxide (ClO2 ), sodium hypochlorite (NaClO) or the relatively new one peracetic acid (PAA). The freshwater bivalves ( Dreissena polymorpha ) being selected as biomarker, have the unique ability to accumulate pollutants. Freshwater bivalves were maintained in surface water containing each disinfectant individually (1–2 mg/L). Following an exposure period up to 20 days during the fall period, microsomes were collected from the mussels, then tested for various monooxygenases. Strong CYP inductions were observed. These data indicate that drinking water disinfection generates harmful DBP mixtures capable of determining a marked perturbation of CYP-supported reactions. This phenomenon, being associated to an increased pro-carcinogen bioactivation and persistent oxidative stress, could provide an explanation for the observational studies connecting the regular consumption of drinking water to increased risk of various cancers in humans. Highlights: Xenobiotic metabolism in mollusks exposed to disinfected surface water was evaluated. Water was disinfected with ClO2, NaClO or peracetic acid. Monooxygenases were measured in microsomes from mussel tissue. Strong induction of xenobiotic bioactivating enzymes was observed. Our results support the increased cancer risk observed in drinking water consumers.